Analysis of 28 antiretroviral drug dispensing units in the state of Ceará - Francisco A. PAULA-; Ana C. BRITO-PASSOS; Maíra B. PEREIRA; Régis B. SILVA; Marta M. FRANÇA FONTELES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objective: To characterize the physical structure of antiretroviral Drug Dispensing Units (DDU) as well as the conditions of service offered to People Living with HIV/SIDA (PLHS). Methods: This is a descriptive, quantitative and exploratory study. Data collection occurred from a semi-structured form composed of 46 questions that was sent to the e-mails of the responsible for Antiretroviral (ARV) dispensing services, containing questions related to human resources and infrastructure characteristics of the units. Results: A total of 28 DDU participated in the study. It was observed that 71.4% (n=20) of these were implanted in replace assistance by care for patients  with Sexually Transmitted Infections (STI) and Acquired Immunodeficiency Syndrome (SIDA) associated with Human Immunodeficiency Virus (HIV) Infection. Regarding the dispensing area of supplies and medicines, this was higher than 14m² in 80% and higher than 5m² in 90% of the sample studied. All units used the logistical drug control system for dispensing control; however, not all professionals in the units were able to operationalize it. Additionally, it was found that in 28.6% (n=8) of the DDU the waiting room/corridor was not adapted for people with disabilities, besides not having priority service as provided by law. It is also emphasized that, in 35.7% (n=10) of the services, the counter where the ARV were dispensed did not facilitate direct contact with the PLHA. In addition, about 29.0% (n=8) of the services had individual service counters with table and chairs available to users and in 60.7% (n=17) there were only counter/counter for service. Also, grids were found in the service desk, separating the attendant from the user in 71.4% (n=20) of the services. The room for individualized service and pharmaceutical clinical care was present in only 32.2% (n=9) of the services. Conclusion: It is suggested that there are adjustments in the physical structure of the units, as well as the need is urgent for individualized and private service, according to the specificities of each service, in order to strengthen the direct relationship between pharmacists and patients and, in particular, ensure humanized assistance.